Sodium butyrate alleviates fructose-induced non-alcoholic fatty liver disease by remodeling gut microbiota to promote γ-amino butyric acid production - Qu Chen; Lei Wu; Aijia Zhang; Chen Wu; Liuping Cai; Yingping Xiao; Yingdong Ni (Food Science and Human Wellness)
Sodium butyrate (NaB) can regulate lipid metabolism and inhibit hepatic steatosis. This study aimed to investigate whether NaB can alleviate fructose-induced hepatic steatosis via remodeling the gut microbiota and evaluate the anti-fatty liver mechanisms. The results showed that NaB and NaB-remodeled gut microbiota significantly alleviated fructose-induced hepatic steatosis and increased plasma uric acid and fructose levels. Furthermore, both NaB and NaB-remodeled gut microbiota increased the abundance of Lactobacillus and altered the levels of plasma amino acids (upregulating gamma-amino butyric acid (GABA) and downregulating L-glutamic acid and L-arginine) in fructose-exposed mice. The correlation analysis showed that GABA levels positively correlated with Lactobacillus abundance, and increased GABA levels might promote the reduction of the hepatic triglyceride content. Further studies confirmed that GABA significantly reduced lipid deposition in mouse hepatocytes induced via fructose pretreatment in vitro. These findings suggested that NaB could ameliorate fructose-induced hepatic steatosis by regulating gut microbiota.